HUBUNGAN GAYA MANAGEMEN KONFLIK KEPALA RUANGAN DENGAN STRES KERJA PERAWAT DI RUANGAN PINERE RS X - Sri Muharni; Umi Eliawati; Reny Wahyuni (Jurnal Keperawatan Abdurrab, 2022)
Most human resources who interact directly with patients are nurses, so that the quality of service carried out by nurses can be assessed as an indicator of the good and bad services in the hospital. This study uses a quantitative research method through a cross sectional approach. The research population was nurses in the pinere room of X hospital. The sampling technique used was total sampling as many as 41 people. The research variable is the room manager conflict management style, with the work stress of nurses in the X hospital. The research instrument usedwas a questionnaire. The results obtained were 31 people (71.6%) had a high conflict management style and 10people (24.4%) had a low management style. As many as 29 people (70.7%) had moderate work stress, 8 people(19.5%) had low stress and 4 people (9.8%) had severe stress. With this phenomenon, the leadership style has an indirect relationship with the work stress of nurses in the pinere room of X hospital.